2007
DOI: 10.4049/jimmunol.179.4.2318
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sjögren’s Syndrome in Nonobese Diabetic-Derived Autoimmune-Prone C57BL/6.NOD-Aec1Aec2 Mice Is Dependent on Complement Component-3

Abstract: The role of complement in the etiology of Sjögren’s syndrome (SjS), a human autoimmune disease manifested primarily by salivary and lacrimal gland dysfunction resulting in dry mouth/dry eye syndrome, remains ill-defined. In the present study, we examined the role of complement component-3 (C3) using a newly constructed C3-gene knockout mouse, C57BL/6.NOD-Aec1Aec2.C3−/−. Inactivation of C3 in the parental C57BL/6.NOD-Aec1Aec2 strain, a model of primary SjS, resulted in a diminished or total absence of both pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 45 publications
1
36
1
Order By: Relevance
“…A preliminary experiment was performed using samples from two NOD males and two NOD females to quantify peptide cleavage at various incubation time points (0 min, 5 min, 30 min, 2 h, 6 h, 16 h; data not shown). Although not reported in previous studies (34,45,46), we observed a sex bias for peptide cleavage such that male saliva cleaved peptide more quickly than female saliva, presumably owing to male saliva containing a higher concentration of PSP protease (Fig. 4B, 4C).…”
Section: Severity Of Sialadenitis But Not Insulitis Is Reduced In Ncontrasting
confidence: 70%
See 2 more Smart Citations
“…A preliminary experiment was performed using samples from two NOD males and two NOD females to quantify peptide cleavage at various incubation time points (0 min, 5 min, 30 min, 2 h, 6 h, 16 h; data not shown). Although not reported in previous studies (34,45,46), we observed a sex bias for peptide cleavage such that male saliva cleaved peptide more quickly than female saliva, presumably owing to male saliva containing a higher concentration of PSP protease (Fig. 4B, 4C).…”
Section: Severity Of Sialadenitis But Not Insulitis Is Reduced In Ncontrasting
confidence: 70%
“…Alternatively, ANAs do not appear to have a direct role in SjS-like disease in NOD mice (43); however, our observed increase in ANA production suggests that the B cell compartment of NOD.NZW-Chr7 female mice may be adversely affected by the congenic interval. A potential reservoir of autoreactive B cells is the MZB population (59), which has been implicated in mouse models of SjS-like disease (46,53). MZBs are also increased in NOD mice compared with non-autoimmune-prone mouse strains (60,61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expansion of MZ B cells in NOD mice has been associated with various autoimmune pathologies (12)(13)(14)(15)(16). However, the cause of their expansion in this strain was not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…This includes studies that show the following: 1) the MZ B cell subset undergoes a large secondary expansion prior to the onset of disease, which is associated with their aberrant migration into the pancreas and its draining lymph nodes (LN) (12); 2) transgenic B cell clones specific for the primary T1D autoantigen insulin are preferentially selected into the MZ subset (14); 3) MZ B cells in NOD mice have the capacity to present insulin to autoreactive CD4 + T cells as effectively as the FO subset (12); and 4) preferential depletion of this subset using an anti-CD21/35 mAb significantly decreased the incidence of cyclophosphamide-induced T1D in NOD mice (15). In addition, accumulation of MZ B cells has also been associated with pathology causing Sjögren's syndrome in nonautoimmune-prone C57BL/6 (B6) mice containing the Aec1 and Aec2 disease susceptibility loci from NOD mice (16).…”
mentioning
confidence: 99%